THE INFLUENCE OF CONFLICT MANAGEMENT SKILLS TRAINING TOWARD LEADERS’ EMOTIONAL INTELLIGENCE IN MAKING DECISION - Siti Nurhidayah; Asip F. Hadipranata (UIN Sunan Kalijaga, 2013)
This research has aimed to tested the inﬂuence of conﬂict management skills training to increase leader’s emotional intelligence in making decision with one co variable i.e. the big fve personality. The result of this research revealed the big fve personality i.e. neuroticism, extravertion, openness to experience, agreebleaness, and counstiousness inﬂuence emotional intelligence of leader in decision making. That was stated by score of emotional intelligence of leader in decision making within co variable by F = 78.951; p = 0.000 and with co variable by F = 10.365; p = 0.007. The result of this research revealed the existence of interaction between group variable and observed variable that was stated by F = 85.267; p = 0.000. The result showed that control group and experimental group was different. The emotional intelligence in decision making of control group was decreased (from -5.500 to -8.200), while experimental group was increased (from 6.600 to 10.800). To test the differences of alteration pattern of each group, researcher observed F value of between subject effect test. It revealed the difference between experimental groupand control group with F = 114.765; p = 0.000. In this research, the conﬂict management skills training treatment contribution toward the emotional intelligence of leader in decision making is 81.3 %.